The Effect of Work-Family Conflict on Turnover Intention with Organizational Commitment as a Mediating Variable in Employees - Rama Retno Handyka; Pricilia Maharani Eppang; Muhamad Alwi (Indonesian Journal of Business Analytics, 2025)
This research seeks to examine the extent to which work-family conflict affects turnover intention, with organizational commitment serving as a mediating variable, at PT. Kharisma Indah Bestari Sampoerna. A quantitative approach with a correlational design was employed to explore the relationships between variables and predict outcomes. The study involved 99 respondents, and data were gathered through questionnaires. Findings from a simple linear regression analysis demonstrated a significant effect of 5.3% from Work-Family Conflict (X) on Organizational Commitment (Z). Additionally, multiple linear regression analysis showed a significant relationship between Work-Family Conflict (X) and Turnover Intention (Y), as well as between Work-Family Conflict (X) and Organizational Commitment (Z) on Turnover Intention (Y), with an influence rate of 39.6%. The study concludes that organizational commitment plays a crucial role in mitigating the impact of work-family conflict on turnover intention. It also suggests that organizational commitment mediates the relationship with turnover intention, with most employees being influenced by this factor, although a small portion is affected by variables not covered in this research.